Studi Penurunan Kadar Logam Besi (Fe) dan Logam Mangan (Mn) pada Lempung terhadap Perubahan Arus Listrik dalam Solenoida - Zain, Abdul; Muliawan, Arief (INTEK: Jurnal Penelitian, 2016)
In the soil there are many compound of Fe and Mn as well as in the clay. Those two compounds need to be reduced to improve the resistive value of the clay. One method to reduce those compounds is by electromagnetic filter using solenoid. From the experiment circuit, it was found that the resistive value was 4.5 Ohm with maximum current of 5 Ampere. Concentration of Fe and Mn after filtered were 0.46 ppm and 0.40 ppm respectively.